Supplier evaluation and selection : a hybrid model based on DEAHP and ABC - Lee, C. K. M. (2013)
Supplier evaluation and selection are now growing to be an important but complex issue due to the fact that they involve a large number of factors and decisions. These factors have complicated operational and financial implications. Therefore, it is necessary to reconcile many competing objectives before a set of comprehensive and consistent metrics for supplier evaluation and selection can be obtained. In this study, a hybrid methodology combining the data envelopment analytic hierarchy process (DEAHP) and activity-based costing (ABC) was developed for supplier evaluation. The advantages of the proposed approach include increasing suppliers’ overall efficiency and also reducing indirect costs which are related to the quality of the supplier and to their delivery performance record. Using this hybrid model, decisions on supplier selection and order quantity can easily be made within an integrated single objective function which is based on consideration of the budget of the buyer and of the capacity of the supplier. A case study was conducted during this study, demonstrating the performance of this hybrid method, in an electronics manufacturing firm.